Status of Freshwater Mussels (Unionidae) in the French Creek Watershed, USA at the Onset of Invasion by Round Goby, Neogobius melanostomus - Kyle H. Clark (MDPI AG, 2021)
Freshwater mussels are an imperiled group of organisms that are vital to aquatic ecosystems. Services performed by freshwater mussels, coupled with their use for biomonitoring, make them an invaluable asset. Neogobius melanostomus (Round Goby), a recently introduced invasive species to the French Creek watershed, was once restricted to the watershed of Lake Erie in Pennsylvania. The Round Goby’s propensity to consume Dreissena polymorpha (Zebra Mussel) and Dreissena bugensis (Quagga Mussel) in their native habitat raises concerns about this recent introduction into Pennsylvania’s Allegheny River watershed. Since the discovery of their introduction within the watershed, we have followed the range expansion and dispersal rate of Round Gobies, which makes this study unique. The objectives of this study were to quantify baseline data on the contemporary diversity and abundance of unionid mussels in the upper French Creek watershed, and to explore potential habitat factors that influence or limit the size of the mussel populations. We gathered baseline data on freshwater mussel diversity and abundances across eight sites in the French Creek watershed and examined substrate particle size and host availability as potential limiting factors of the freshwater mussel distribution. Freshwater mussel surveys were conducted during the summer months (July–September) of 2017 using area-constrained surveys. Results showed a significant relationship between mussel diversity and substrate particle size (p < 0.05). From the data collected, we were able to calculate population estimates for the species found across the sample sites. Our results regarding the locations of native mussel populations and characteristics of their habitat provide the needed insight for establishing priority areas for the conservation of freshwater mussels, facilitating planning for protection, mitigation, and adaptation as the invasive Round Goby continues its spread.